Analysis of Service Levels in the Development of Infrastructure and Facilities against Minimum Service Standards in Supporting the Quality of Area Facilities Intanjung Piayu District, Batam City - Syafrijal, Syafrijal; Sidabutar, Yuanita FD; Fauzan, Fauzan (Borong Newinera Publisher, 2024)
The government has an important role in providing public services for its people. Every public service provider must have service standards. One form of standard public service is the service of developing facilities and infrastructure. Facilities and infrastructure development services can be divided into nine elements, namely service procedures, suitability of proposals, timeliness, complaint handling, implementing competence, provider competence, development quantity, development quality and development results. The research was conducted in Tanjung Piayu Village, Batam City by direct observation and filling out a questionnaire regarding community perceptions regarding facilities and infrastructure development services. Type of descriptive qualitative research. This study uses minimum service standards (SPM) and index analysis. The research sample was 80 respondents. The results of the research show that the facilities and infrastructure development services owned by respondents are considered to be in good condition, with a service unit IKM of 76.90. However, there is a mismatch between the results of the assessment and real conditions, there are three elements of services for the construction of facilities and infrastructure that are in poor condition, namely timeliness, service procedures, and construction quantity. So, There is a need for re-management of existing facilities and infrastructure development services in order to further improve the quality of public services provided.